Transfer to the continuum of 11Be with the application of ab-initio S-matrix. (December 2020) - Carbone, D; Bonaccorso, A; Cappuzzello, F; Cavallaro, M; Hupin, G; Navrátil, P; Quaglioni, S
Abstract: The 9 Be( 18 O, 16 O) 11 Be two-neutron transfer reaction at 84 MeV is measured at forward angles to explore the continuum of 11 Be nucleus. Transfer-to-the-continuum (TC) reaction calculations are applied using for the first time an ab-initio S -matrix. It is derived from the ab-initio no-core shell model with continuum (NCSMC) method, recently used to describe the bound and continuum spectrum of 11 Be. Previously known levels are confirmed and theoretical and experimental evidence for a 9/2+ state at Ex = 5.8 MeV is given, whose configuration is thought to be 10 Be(2 + ) + n(d5/2 ).